OCTAHEDRAL CATION ORDERING OF ILLITE AND SMECTITE. THEORETICAL EXCHANGE POTENTIAL DETERMINATION AND MONTE CARLO SIMULATIONS - Sainz-Diaz C.I.; Hernández-Laguna A.; Palin E.J.; Dove M.T. (My University, 2003)
The distributions of Al3+/Mg2+ and Al3+/ Fe3+ were studied in the octahedral sheet of illites and smectites. Cation exchange interaction parameters J i , as first, second, third and fourth neighbours were calculated by means of empirical interatomic potentials. Several compositions with different interlayer cations and tetrahedral charge were studied in both Al/Mg and Al/Fe systems. The values of J i parameters were similar in all Al/Mg samples. From these J i values, a strong trend to form AlMg pairs was observed in the Al/Mg system. In the Al/Fe system, the values of J i are very small, indicating no preference for Al/Fe mixing. From these J i parameters, Monte Carlo simulations of octahedral cation ordering were performed. In the Al/Mg system, an order/disorder phase transition was observed obtaining a fully ordered distribution without presence of an MgMg pair, according to experimental data. Similar phase transitions were observed for the octahedral compositions Al/Mg 1/1 and 3/1. In the Al/Fe system an order/disorder phase transition was also detected but at very low temperature for illite and smectite. Complete Al/Fe mixing is observed in the most stable ordered distribution. This is consistent with experimental results for synthetic Fe/Al smectites.
Keywords: Cation ordering; Illite; Smectite; Monte Carlo simulations